Proceedings of the 3rd International Conference on Social Sciences (ICSS 2020) 2020
DOI: 10.2991/assehr.k.201014.173
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Marketing Mix 4P Towards Marketing Product Performance Of Tenun Ikat Small Industry In Bandar Kediri

Abstract: Customers' needs are increasing, and there is make more competition with similar products. In this case, it can bead dressed in marketing concept, it means a business must has a strategy to achieve objectives and provide satisfaction customers and provide of the results form of salaries to business developers. Every business running by a developer must have an effort, have a concept of strategy that can carry out activities of adaptation to the environment that currently continues to experience changes such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Some scholars have verified that lower price is beneficial to customers' purchasing intention because of the research results of Basirat 2021. However, Ana, Xueqian Cao, and Desi argued in their research that the customer's intention to purchase is unaffected by price [11][12][13]. In the research of reflection on purchase decisions for Ulos Handicraft Products, Desi found that the amount of customer purchases is independent of the price charged for Ulos products, the price has no impact on consumers' decisions to buy those products [13].…”
Section: Important Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Some scholars have verified that lower price is beneficial to customers' purchasing intention because of the research results of Basirat 2021. However, Ana, Xueqian Cao, and Desi argued in their research that the customer's intention to purchase is unaffected by price [11][12][13]. In the research of reflection on purchase decisions for Ulos Handicraft Products, Desi found that the amount of customer purchases is independent of the price charged for Ulos products, the price has no impact on consumers' decisions to buy those products [13].…”
Section: Important Resultsmentioning
confidence: 98%
“…This argument has been verified by many researchers. In 2020, Ana found that the product had an impact on Tenun Ikat Small Industry's marketing product performance in Bandar Kediri while exploring the impact of the Marketing Mix Theory on this sector of the economy [11]. One year later, Xueqian Cao found that Zoom Video Communications attract more customers compared to Google meet during the pandemic as its product meet the demand of the customers [12].…”
Section: Important Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This aims to describe easier access for consumers and customers who will buy and make purchases of products (20). The head office, warehouse, factory, physical store, branch office, and branch store are all included in this component of the marketing mix (21). Currently, business actors do not have to place their head office, factory, and physical store in one location.…”
Section: Introductionmentioning
confidence: 99%